Synthesis and Characterization of Ni(II) Schiff Base Complex as a Precursor for NiO Nanoparticles and an Investigation of Their Corrosion Inhibition - Raji, Shahad Qasim; Bader, Ali Talib (Science and Technology Indonesia, 2024)
This study first aimed to synthesize and characterize a [Ni(C14H13NO2)(OAC)2(H2O)2] via the preparation of a ligand, coordination with Ni(II) ions, and full characterization, such as "FTIR, 1H and 13C-NMR, UV-Visible spectroscopy; and ESI-mass spectrometry" The Nickel complex was then used as a precursor to prepared NiO Nps by calcination at 450°C. The phase purity, crystalline structure, and morphological characterizes of the NiO nanoparticles were investigated via X-ray diffraction (XRD), FESEM, and FTIR spectroscopy, revealing them to be cubic system with an average crystalline is 26 nm. The preparation technique is facile, cost-effective, and rapid and suitable for generating NiO nanoparticles for use in industrial processes. Further, the corrosion inhibition effectiveness of all synthesized compounds on mild steel in 1 M HCl was evaluated. Their inhibition efficiencies were determined via potentiodynamic polarization studies, revealing the highest inhibition efficiency for the NiO nanoparticles compared to the Nickel complex and free a ligand.